Kinetic models for the Pt/CeO₂ catalysed water-gas shift reaction - Brown, Darryl Edward (Centre for Catalysis Research, 2018)
As the global population grows, so does the world's demand for energy. Consequently, there exists an increased interest in the development of fuel cells for power generation due to their low greenhouse gas emissions. For fuel cells to be a successful power source, a reliable hydrogen source is required. Ultimately, the goal is for hydrogen to be supplied from renewable energy technology however, this type of technology is currently not mature enough to meet the continuous demand of the world's energy systems. Producing hydrogen from fossil fuels can be seen as a temporary solution while further advances are made in developing renewable hydrogen infrastructure. A fuel processing train, therefore, remains an important alternative to producing hydrogen. A fuel processing train converts fossil fuels into hydrogen for use in fuel cells and eliminates the need for hydrogen storage as hydrogen is produced on demand. Currently, the water-gas shift (WGS) reactor is one of the largest components in a fuel processing train and thus opportunity exists to reduce the size of this reactor. To design future WGS catalysts and an optimised fuel processor, the reaction kinetics taking place must be understood and quantified. In this study, kinetic measurements were conducted at 2 bar(a) and across a temperature range of 270 - 300 °C using 16 parallel fixed bed reactors (high throughput experimentation) over a 0.5 wt% Pt/CeO₂ catalyst. The feed composition was varied over the ranges 2 - 12 mol% CO, 20 - 45 mol% H₂O, 4 - 15 mol% CO₂ and 25 - 55 mol% H₂. An online micro gas chromatograph (μGC) was used to analyse the dry gas composition. Fitting of experimental data to various kinetic models was accomplished with the gPROMS software package. An initial evaluation of several Langmuir-Hinshelwood (LH) type mechanisms to two data sets obtained from literature was undertaken to evaluate the strengths and weaknesses of different kinetic expressions. The results of the initial evaluation indicate that a dual-site mechanism with an intermediate species results in the best fit for reducible supports, while a single site mechanism offers a better fit for non-reducible supports. For both kinetic models, the formation of the intermediate species is most likely to be the rate determining step. A power-rate law empirical rate expression and a LH type rate expression were both found to predict the WGS outlet composition well within 10 % error at 2bar(a). The apparent activation energy of the reaction was determined to be 110 kJ/mol. This value was confirmed to be constant, throughout the range of conditions evaluated, by means of a classical Arrhenius analysis. Simulations of increasing total system pressure, using both the empirical and "best fitting" LH model, indicate a significant pressure effect for the LH type equation, whereas the power-rate law empirical equation predicts a small, negative effect on the reaction rate with increaseing pressure. Consequently, further experiments were conducted to determine the true effect of pressure. It was found that increasing system pressure increased the WGS reaction rate, which has also been reported by Twigg (1989:288). Only the LH type rate expression was able to predict this. It is therefore recommended that either the power-rate law empirical rate expression or the LH type rate expression be used to predict the WGS outlet composition when operating below 2 bar(a). Furthermore, when predicting reaction rates outside of the window in which the rate equations were derived, it is recommended that the LH model be used as it is expected to give a better prediction as it is based on fundamental steps.